Efficacy and safety of high-intensity focused ultrasound ablation under general anesthesia in older hepatocellular carcinoma patients - Xie, Siyu; Ran, Lifeng; Yang, Wei; Zhou, Kun; Jin, Chengbing; Zhu, Hui (Frontiers in Oncology, 2025)
BackgroundOlder patients often have comorbidities, leading to a higher risk of delayed recovery while under general anesthesia. High-intensity focused ultrasound (HIFU) for patients with hepatocellular carcinoma (HCC) usually requires general anesthesia to alleviate procedure-related pain and ensure immobilization. This study aimed to evaluate the safety and efficacy of HIFU for the treatment of older patients with HCC, and to explore the associated prognosis and risk factors.MethodsA total of 174 patients with HCC who underwent HIFU were enrolled in this study and divided into three age groups: <60 years (n=100), 60–74 years (n=55), and ≥75 years (n=19). The risks of general anesthesia associated with HIFU were observed, and the ablation effects of HIFU were evaluated using contrast-enhanced CT or MRI. Survival analysis, prognosis and risk factors were analyzed.ResultsThe prevalence of comorbidities was 73.68%, 52.72%, and 26.00% in patients aged ≥75 years, 60–74 years, and <60 years, respectively. The difference between the three groups was significant (P < 0.001). The rates of complete response (CR), partial response (PR), and ORR were 25.61%, 46.34%, and 71.95% in patients aged <60 years, 34.04%, 40.42%, and 74.46% in patients aged 60–74 years, and 12.50%, 62.50%, and 75.00% in patients aged ≥75 years, respectively. 1-year and 2-year overall survival (OS) rates in patients aged <60, 60–74, and ≥75 years were 78.4% and 70.5%, 84.5% and 75.3%, and 72.4% and 43.4%, respectively. There were no significant differences in ORR and OS between the three groups (P = 0.937 and 0.055, respectively). No significant difference of the median interval time of anesthesia recovery between three groups occurred (P = 0.208) and no other anesthesia-related complications were observed. CNLC stage III was an independent prognostic factor (P = 0.049). AFP ≥20 ng/mL was an independent risk factor (P = 0.016), whereas the combination of other local treatment methods was a protective factor (P = 0.016).ConclusionsHIFU ablation under general anesthesia for older HCC patients is safe, feasible and effective.